1992
DOI: 10.1021/bi00122a016
|View full text |Cite
|
Sign up to set email alerts
|

Titration calorimetric and differential scanning calorimetric studies of the interactions of n-butanol with several phases of dipalmitoylphosphatidylcholine

Abstract: The interactions of n-butanol with dipalmitoylphosphatidylcholine (DPPC) were studied using titration calorimetry and differential scanning calorimetry (DSC). DSC results indicated that n-butanol induces the interdigitated phase in DPPC above 10 mg/mL butanol. A new application of titration calorimetry for measuring partition coefficients of nonsaturating solutes into lipids was developed. The partition coefficients and the heat of binding of n-butanol into DPPC were measured for the L beta', P beta', L alpha,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
72
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 27 publications
11
72
1
Order By: Relevance
“…Comparatively, the n-butanol system exhibited "stunted" biphasic behavior. From this data it was concluded that the threshold concentration for n-butanol is 0.16 M, in agreement with previous studies on the DPPC system [6,14,15].…”
Section: Dscsupporting
confidence: 91%
“…Comparatively, the n-butanol system exhibited "stunted" biphasic behavior. From this data it was concluded that the threshold concentration for n-butanol is 0.16 M, in agreement with previous studies on the DPPC system [6,14,15].…”
Section: Dscsupporting
confidence: 91%
“…It's worth emphasizing that the occurrence of the interdigitated phase is expected at alcohol concentrations above a threshold value equal to 2:1 alcohol/lipid ratio, as it has been observed for DPPC/n-butanol system [6]. This is just the concentration of the lipid/alcohol samples which have been investigated in this paper.…”
Section: Resultsmentioning
confidence: 65%
“…More precisely, experiments on phospholipid membranes have shown that alcohol can induce the interdigitated phase [3,4,5] that, at high alcohol concentrations, replaces the ripple gel phase [5,6]. The interdigitated phase is characterized by a greater order compared to the ripple phase [7].…”
mentioning
confidence: 99%
“…The principal of these methods is to fit the experimental data in an equation relating equilibrium constant, molar enthalpy of binding and reactants concentration. The Wiseman method [45] for data analysis has extensively used for ligand binding studies by ITC and a computer program is needed for using this method [61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%